ANALYSIS OF VEGETATION IN SPECIAL PURPOSE FOREST OF TUMBANG NUSA, JABIREN RAYA SUBDISTRICT, CENTRAL KALIMANTAN - Sosilawaty, Sosilawaty; Yanarita, Yanarita; Andrean, Tudi (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
Forests are natural resources that provide double benefits, direct and indirect benefits. The direct benefit of forest is as a source of various types of goods, such as woods, saps, barks, leaves, roots, fruits, and flowers that can be used directly by humans or become raw materials for various industries. The special-purpose forest of Tumbang Nusa is a secondary peat swamp forest. Peat swamp forest is a forest formation quite widespread in Indonesia. The term arises because swamp forest and peat forest are basically always adjacent and often do not have clear boundaries that are so-called peat swamp forests. The purpose of this study was to find out the structure and species composition (species dominance, species diversity, species richness and species evenness) of secondary peat swamp forest vegetation in special-purpose forest of Tumbang Nusa, Jabiren Raya Subdistrict, Central Kalimantan Province. The results of the study showed that the vegetation structure by diameter classes was dominated by the vegetation with small diameter (0-9 cm) and by height classes was dominated by the vegetation with low height-class (0-5 m). The diversity of vegetation in the study plots showed that there were 42 species of vegetation consisting of 24 families, and the most common species found were the family of Lauraceae (5 species), Dipterocarpaceae (4 species), Myristicaceae, Myrtaceae and Guttiferae (3 species), Podocarpaceae, Apocynaceae, Ebenaceae, Moraceae and Annonaceae (2 species), and a few other family (one species of each). The species diversity at seedling and sapling stages was moderate (H' ≥ 2 and < 3) while the diversity at pole and tree stages was low (H' < 2). The values of species richness index at seedling, sapling and pole stages were moderate (R = 3.5 - 5.0) while at the tree stage was relatively low (R > 3.5). The species evenness index at seedling and sapling stages was high (E > 0.6) while at the pole and tree stages moderate (E = 0.3 to 0.6).